PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE 2008-2010 - Sarana Hadi Wibowo, 08.3503.0704; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2013)
This research aim to analyze capital structure influence, firm size and company growth to profitability at manufacturing business in Indonesian Stock Exchange. Population in this research is company of manufacture sector which enlist in Indonesian Stock Exchange. Sample Research with criterion which have been determined to be to be obtained by counted 53 manufacturing company which publicâs company in Indonesia Stock Exchange, with data pooled method or panel data during year 2008 - 2010, so that the amount of sample ( n) = 53 x 3 = 159. While used by method is multiple linier regression. Result of examination in obtaining that no influence which isratio significant owe short-range with capital; long-range debt ratio with capital; and total debt with capital to profitability by partial. Other result shows there is influence which firm size measure significant to profitability by partial.Key words : Capital Structure, firm size, company growth, and profitability